Application of Vector Sensors to Acoustic Surveillance of a Public Interior Space - ŁOPATKA, Kuba; KOTUS, Józef; CZYŻEWSKI, Andrzej (Archives of Acoustics, 2011)
A method for precise sound sources detection and localization in interiors is presented. Acoustic vector sensors, which provide multichannel output signals of acoustic pressure and particle velocity were employed. Methods for detecting acous- tic events are introduced. The algorithm for localizing sound events in the audience is presented. The system set up in a lecture hall, which serves as a demonstrator of the proposed technology, is described. The accurracy of the proposed method is evaluated by the described measurement results. The analysis of the results is fol- lowed by conclusions pertaining the usability of the proposed system. The concept of the multimodal audio-visual detection of events in the audience is also introduced.